Radical Copolymerization of Vinyl Ethers and Cyclic Ketene Acetals as a Versatile Platform to Design Functional Polyesters. Issue 52 (4th December 2017) - Tardy, Antoine; Honoré, Jean‐Claude; Tran, Johanna; Siri, Didier; Delplace, Vianney; Bataille, Isabelle; Letourneur, Didier; Perrier, Josette; Nicoletti, Cendrine; Maresca, Marc; Lefay, Catherine; Gigmes, Didier; et al.
Abstract: Free‐radical copolymerization of cyclic ketene acetals (CKAs) and vinyl ethers (VEs) was investigated as an efficient yet simple approach for the preparation of functional aliphatic polyesters. The copolymerization of CKA and VE was first predicted to be quasi‐ideal by DFT calculations. The theoretical prediction was experimentally confirmed by the copolymerization of 2‐methylene‐1, 3‐dioxepane (MDO) and butyl vinyl ether (BVE), leading to r MDO =0.73 and r BVE =1.61. We then illustrated the versatility of this approach by preparing different functional polyesters: 1) copolymers functionalized by fluorescent probes; 2) amphiphilic copolymers grafted with poly(ethylene glycol) (PEG) side chains able to self‐assemble into PEGylated nanoparticles; 3) antibacterial films active against Gram‐positive and Gram‐negative bacteria (including a multiresistant strain); and 4) cross‐linked bioelastomers with suitable properties for tissue engineering applications. Abstract : VE/CKA, the ideal couple : The radical copolymerization between cyclic ketene acetal (CKA) monomers and vinyl ether (VE) derivatives led to a new and easy way to prepare homogeneously functionalized aliphatic polyesters (left to right in picture: nanoparticles, bioelastomers, antibacterial surfaces).